Literasi Politik Melalui pendidikan Demokrasi Partisipatif Dalam Masyarakat Gampong - Bahagia, Bahagia; Fadhil, Fadhil; Khalisni, Khalisni; Sari, Novita; Faraidiany, Maghfira; Munawarah, Munawarah (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
The problem that occurs in the process in Lamreudeup Dalam Village is the lack of women's involvement in politics, such as candidates for village heads as political positions from women who are promoted to village heads or Keuchik. Meanwhile, the village that will be led until 2025 is still led by a Keuchik, with details of 1 Keuchik, 1 Serdes, 4 Hamlet Heads and 4 heads of affairs. The purpose of community service in I Political Literacy Through Participatory Democracy Education based on Village Community, which was carried out in Lamreudeup Village, Baitussalam District, Aceh Besar Regency, Aceh Province was carried out on Tuesday, June 3, 2025, in Lamreudeup Village. The stages of the process of implementing activities carried out in Lamreudeup Village, Baitussalam District, Aceh Besar Regency with a Qualitative approach such as documents with descriptive Qualitative directly they felt happy that the activities carried out went well and in accordance with what was expected by the people of Lamreudeup Village, Baitussalam District, Aceh Besar Regency